Evaluation of physicochemical properties and functional potential of analog rice based on commercial flours of porang tuber and gembili as an alternative carbohydrate food source - Salma Widya Azhari; Sri Anna Marliyati; Hardinsyah Hardinsyah (AcTion: Aceh Nutrition Journal, 2025)
Indonesia is one of the countries that produces porang and gembili tubers that can be processed into value-added food products. One innovation that can be developed is the analog rice made from these two tubers. Porang and gembili tubers are known to contain bioactive compounds and dietary fiber that provide functional benefits, such as lowering blood glucose levels, improving lipid profiles, and improving digestive tract health. This study aimed to evaluate the physical and proximate qualities of three analog rice formulations using commercial porang and gembili flours. The experimental design used was a Completely Randomized Design (CRD) with two replications, conducted from August to December 2024 at the Technopark Laboratory (Faculty of Agricultural Technology) and Nutrition Analysis Laboratory (Department of Community Nutrition, FEMA IPB). The formulations had porang and gembili ratios of F1 (75:25), F2 (50:50), and F3 (25:75). Data were analyzed using One-Way ANOVA preceded by variance homogeneity testing, followed by DMRT multiple range test. The results showed that cooking time and bulk density differed significantly between F1, F2, and F3. The expansion ratio, degree of breakage, and hardness differed significantly among F3, F1, and F2. F3 exhibited the highest brightness (L*) value. Proximate analysis revealed significant differences in ash, moisture, protein, fat, and carbohydrate contents among all formulations. The F3 formulation, which had a higher proportion of gembili, demonstrated the greatest potential as a staple carbohydrate source. However, further sensory and consumer acceptability improvements are needed.